Sarcoid-like reaction associated with lung adenocarcinoma: A case report. (March 2019) - Tan, Qiao Li; Leow, Leong Chai; Haja Mohideen, Salahudeen Mohamed; Sewa, Duu Wen
A 71-year-old woman with a history of left lower lobe lobectomy 4 years ago for adenocarcinoma of the lung presented with new mediastinal and bilateral hilar lymphadenopathy on surveillance imaging, suspicious for disease recurrence. She underwent an endobronchial ultrasound-guided transbronchial needle aspiration of the lymph nodes and histology yielded non-necrotizing epithelioid granulomas with no evidence of malignancy. A diagnosis of sarcoid-like reaction associated with lung adenocarcinoma was made. The significance of this rare condition is discussed.